DAYA TERIMA MAKANAN FORMULA IKAN DAN FORMULA KACANG HIJAU PADA BALITA GIZI KURANG DI WILAYAH KERJA PUSKESMAS KALUMATA KOTA TERNATE TAHUN 2018 - Nizmawaty Amra; Juhartini Juhartini (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2018)
Toddlers aged 1-5 years (preschool age) is the age in the life cycle where growth is not as fast as in infancy, but many activities, a defining period in growth and development, which will be the basis for the formation of whole people. This study aims to determine the acceptability of fish formula foods and green bean formulas in underfive toddlers in the working area of ​​the health center kalumata Ternate city. The research design used was quasi-experimental. The number of samples was 22 under-five children under five. The results of this study indicate that the highest category of acceptance of good fish formula food as many as 9 respondents (81.8%), less good as 2 respondents (18.2%), while good mung bean formula food as many as 10 respondents (90.9% ), less than 1 respondent (9.1%). Thus it is concluded that most toddlers can receive well the fish formula and green bean formula. This formula can be given as an additional food to overcome and prevent malnutrition